- #1

- 148

- 5

Thank you.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- I
- Thread starter Gjmdp
- Start date

- #1

- 148

- 5

Thank you.

- #2

fresh_42

Mentor

- 15,772

- 14,077

- #3

- 148

- 5

Thank you for your answer. How can you prove that?and##M## is regularand##Mu=Mv## then ##u=v##.

- #4

fresh_42

Mentor

- 15,772

- 14,077

Your reasoning is correct if those assumptions are given.Thank you for your answer. How can you prove that?

- #5

Mark44

Mentor

- 35,431

- 7,295

I think more usual terms forIf ##n=m##and##M## is regularand##Mu=Mv## then ##u=v##.

##Mu = Mv \Rightarrow Mu - Mv = 0 \Rightarrow M(u - v) = 0##Thank you for your answer. How can you prove that?

Assuming M is invertible, then ##M^{-1}M(u - v) = M^{-1}0 = 0##, or ##u - v = 0##

Share:

- Replies
- 8

- Views
- 4K